2013
DOI: 10.1002/jgrd.50543
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation extremes over the continental United States in a transient, high‐resolution, ensemble climate model experiment

Abstract: [1] Understanding future changes in the frequency, intensity, and duration of extreme events in response to increased greenhouse gas forcing is important for formulating adaptation and mitigation strategies that minimize damages to natural and human systems. We quantify transient changes in daily-scale seasonal extreme precipitation events over the U.S. using a five-member ensemble of nested, high-resolution climate model simulations covering the 21st century in the Intergovernmental Panel on Climate Change (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 118 publications
5
87
1
Order By: Relevance
“…Except for APHRODITE, ERA-Interim, and JRA55, the rest shows a remarkable increasing trend over central India, which is consistent with the finding of Rana et al (2015) and Prakash et al (2014). Singh et al (2013) found that APHRODITE has opposite trend signs for extreme precipitation intensity from the 2000s onwards when compared with the IMD dataset (2140 rain-gauge station).…”
Section: Interannual Variabilitysupporting
confidence: 85%
See 1 more Smart Citation
“…Except for APHRODITE, ERA-Interim, and JRA55, the rest shows a remarkable increasing trend over central India, which is consistent with the finding of Rana et al (2015) and Prakash et al (2014). Singh et al (2013) found that APHRODITE has opposite trend signs for extreme precipitation intensity from the 2000s onwards when compared with the IMD dataset (2140 rain-gauge station).…”
Section: Interannual Variabilitysupporting
confidence: 85%
“…To define daily precipitation extremes, we used the percentile approach (Diffenbaugh et al 2005;Malik et al 2012;Kopparla et al 2013;Singh et al 2013). In particular, for a percentile threshold of p, we find the pth percentile of the distribution of daily rainfall over all the grids over the Asian domain.…”
Section: Methodsmentioning
confidence: 99%
“…Projected decreases in precipitation concur with projections by Schoof [2], who reported moderate precipitation decreases for the Southern USA based on the fifth assessment report (AR5) [16]. Similarly, Singh et al [45] projected strong dry trends in seasonal precipitation for the Southwest USA. Moreover, average temperature (Tmin and Tmax) projections show consistent increases during all three periods; twofold increases in Tmin and Tmax are projected in the 2090s compared with projected increases in the 2020s and 2055s (Figure 4b,c).…”
Section: Seasonal Changes Of Projected Climatesupporting
confidence: 80%
“…The findings of the current study are in agreement with those of Schoof [2], who reported a projected decline in annual total precipitation in the Southwest USA. Similarly, Singh et al [45] reported negative anomalies of total annual precipitation in the Southwestern USA. However, positive increases in precipitation were reported in areas with monsoon climates, such as Nepal [6].…”
Section: Future Climate Projections and Uncertainties Of Gcmsmentioning
confidence: 86%
“…Understanding future changes in the frequency, intensity, and duration of extreme events is important when formulating adaptation and mitigation strategies that minimize damage to natural and human systems [3]. Indeed, Zubieta & Saavedra [4] point out that one of the most important aspects of climate change that requires in-depth research is the characterization of precipitation in time and space.…”
Section: Introductionmentioning
confidence: 99%